Effect of Heat Stress on Sperm Production, Oxidative Markers and their Association in Native Breeding Bulls - Dhami, Arjun J; Suthar, Vishal S; Chaudhari, Dinesh V; Hadiya, Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The objective of the study was to evaluate the effect of climatic conditions on fortnightly semen quality and its oxidative markers, and to evaluate the correlation between them in zebu cattle and buffalo breeding bulls under weekly twice semen collection schedule. The macro- (observatory; daily; n=330) and micro- (bull shed; hourly; n=8540) climatic parameters, viz., ambient temperature (AT °C) and relative humidity (RH %) were measured during Jan to Dec 2018 and temperature humidity index (THI) was generated. There were high associations between micro and macro AT (r=0.982), RH (r=0.897) and THI (r=0.985). Overall, micro-AT was 1.20°C higher, micro-RH was 5.42% lower and the micro-THI was 0.50 higher than the corresponding macro-climatic parameters. Therefore effect of micro-climatic AT, RH and THI was evaluated on biweekly collected 26 ejaculates of three bulls each of Surti, Murrah buffalo and Gir cattle breeds. The macro and microscopic parameters of semen and oxidative markers in seminal plasma, viz., catalase, lipid peroxidation (MDA), superoxide dismutase (SOD) and glutathione peroxidase (GPx) were determined. During the day 72.6% of hours, bulls experienced stress (THI > 72). No impact of season was observed on seminal attributes and oxidative markers of cattle and buffalo bulls, however correlation coefficients were achieved. The results of our study warrants further investigation on more number of bulls including their semen freezability and fertility